PROBLEMS OF HOUSE ARREST APPLICATION - M. V. Kolesnikov (Russian Journal of Economics and Law)
Objective: to determine the position of house arrest in the system of preventive measures and to identify the main problems of criminal procedural regulation that prevent its broader use during the preliminary investigation and trial. Methods: dialectical approach to the analysis of social phenomena, allowing to view them in static and dynamic aspect; evolutionary-synergetic paradigm, providing the opportunity to explore the phenomenon under investigation with respect to the system, subordinate and coordinating relationships within the system. Dialectical approach and the evolutionary-synergetic paradigm determined the choice of specific methods of research: historical, comparative law (comparative), formal-legal, statistical. Results: the problems arising with application of house arrest are grouped by author, depending on the structure of the provisions of Article 107 of the Criminal-Procedural Code of the Russian Federation. The first group of problems includes the determination of the location of the accused (suspect) under house arrest and the scope of the legal restrictions imposed. The second group includes the establishment of terms of house arrest and their subsequent renewal, or change of the preventive measure. The third group is the identification of persons to which the house arrest will be the best preventive measure. The results of the study allow to make proposals to change the current wording of Art. 107 of the Criminal-Procedural Code of Russia. Scientific novelty: a comprehensive study of current state of the normative-legal regulation of house arrest in the context of its practical application. Practical value: the main provisions and conclusions of the article can be used in scientific and pedagogical activity when considering questions about the nature of preventive measures related to the restraint of personal liberty of the accused.